Analisis Hubungan Antar Luar Negeri Dan Capital Inflow Terhadap Pertumbuhan Ekonomi - Regita Nabila Saragih; Syafita Khairunnisa Pasaribu (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This research aims to analyze the relationship between foreign relations and capital inflow on a country's economic growth. These factors play a crucial role in determining a country's economic performance. The study utilizes macroeconomic data from the period 2010 to 2020 to test the proposed hypotheses. The analysis results indicate a significant positive relationship between foreign relations and economic growth, as well as a strong correlation between capital inflow and economic growth. Furthermore, the research reveals that foreign relations and capital inflow have a significant synergistic impact on economic growth. Policy implications of these findings are discussed in the context of a country's economic development and foreign relations.